Long‐Term Clinical Impact of Adaptation of Initial Tacrolimus Dosing to CYP3A5 Genotype. Issue 9 (8th April 2016) - Pallet, N.; Etienne, I.; Buchler, M.; Bailly, E.; Hurault de Ligny, B.; Choukroun, G.; Colosio, C.; Thierry, A.; Vigneau, C.; Moulin, B.; Le Meur, Y.; Heng, A.‐E.; et al.
Abstract : Pretransplantation adaptation of the daily dose of tacrolimus to CYP3A5 genotype is associated with improved achievement of target trough concentration (C0 ), but whether this improvement affects clinical outcomes is unknown. In the present study, we have evaluated the long‐term clinical impact of the adaptation of initial tacrolimus dosing according to CYP3A5 genotype: The transplantation outcomes of the 236 kidney transplant recipients included in the Tactique study were retrospectively investigated over a period of more than 5 years. In the Tactique study, patients were randomly assigned to receive tacrolimus at either a fixed dosage or a dosage determined by their genotype, and the primary efficacy end point was the proportion of patients for whom tacrolimus C0 was within target range (10–15 ng/mL) at day 10. Our results indicate that the incidence of biopsy‐proven acute rejection and graft survival were similar between the control and the adapted tacrolimus dose groups, as well as between the patients who achieve the tacrolimus C0 target ranges earlier. Patients' death, cancer, cardiovascular events, and infections were also similar, and renal function did not change. We conclude that optimization of initial tacrolimus dose using pharmacogenetic testing does not improve clinical outcomes. Abstract : This study of the long‐term clinical impact of the adaptation of tacrolimus dosing according to CYP3A5 genotype suggests that optimization of the initial tacrolimus dose using pharmacogenetic testing does not improve clinical outcomes after kidney transplantation.